2019
DOI: 10.1371/journal.pone.0218886
|View full text |Cite
|
Sign up to set email alerts
|

Meibomian gland dropout rate as a method to assess meibomian gland morphologic changes during use of preservative-containing or preservative-free topical prostaglandin analogues

Abstract: Purpose To investigate the usefulness of meibomian gland (MG) dropout rate in the evaluation of MG morphological change associated with the use of prostaglandin for glaucoma treatment through the association between MG and the ocular surface parameters and medication duration and presence of preservative. Methods This cross-sectional study was conducted on 88 eyes of 88 patients who were diagnosed with glaucoma and used only Tafluprost as treatment. The patients were di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
12
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 38 publications
(37 reference statements)
1
12
0
1
Order By: Relevance
“…Next, the original color photograph was converted into an 8-bit type image. We then applied automatic threshold identification to discriminate the meibomian gland area from the non-meibomian gland area [26]. The non-meibomian gland area was regarded as the meibomian gland dropout area.…”
Section: Meibomian Gland Morphology Evaluationmentioning
confidence: 99%
“…Next, the original color photograph was converted into an 8-bit type image. We then applied automatic threshold identification to discriminate the meibomian gland area from the non-meibomian gland area [26]. The non-meibomian gland area was regarded as the meibomian gland dropout area.…”
Section: Meibomian Gland Morphology Evaluationmentioning
confidence: 99%
“…The effects of preservatives and antiglaucoma medications on meibomian glands have been previously reported, and are known to cause functional and structural changes in meibomian glands [29][30][31]. Antiglaucoma medications cause subclinical inflammation which results in keratinization of meibomian gland orifice and subsequent stagnation of meibum [29].…”
Section: Discussionmentioning
confidence: 96%
“…Antiglaucoma medications cause subclinical inflammation which results in keratinization of meibomian gland orifice and subsequent stagnation of meibum [ 29 ]. Lee et al demonstrated worsening of lid margin abnormality, expressibility of meibum, and meiboscore in patients using preservative-containing antiglaucoma medications [ 30 ]. However, in our study, the groups with or without antiglaucoma medications only differed in SIT values.…”
Section: Discussionmentioning
confidence: 99%
“…Lee et al reported that the meibomian gland dropout rate caused by glaucoma medication use had a significant correlation with medication duration and preservative status. 29 Finally, there is a possibility that the absence of BAK does not affect the occurrence of side effects in BTFC. Murugesan et al found that there was no significant difference in tear neuropeptide levels and central corneal/confocal corneal subbasal nerve fiber layer density between BAK-containing and BAK-free antiglaucoma therapies.…”
Section: Discussionmentioning
confidence: 99%